Finite-time synchronization and quasi-synchronization of fractional-order fuzzy BAM neural networks with time delays - Zhao, Wei; Zhang, Hongmei; Zhang, Hai; Lu, Qinyun; Cao, Jinde (Nonlinear Analysis: Modelling and Control, 2025)
This paper concentrates on the finite-time synchronization (FTS) and the quasi-synchronization (QS) problems for a kind of fractional-order fuzzy BAM neural networks with time delays (FOFBAMNNs). In order to reach the goals of synchronization, two novel controllers are designed. Then, based on finite-time stability theorem, Lyapunov function theory, and several inequality techniques, through the application of two different designed controllers, several criteria for both FTS and QS are established. Moreover, more precise error level and settling times are given. The effectiveness of the derived criteria is ultimately validated through two simulations.